(untitled) (Bangladesh Journal of Medical Science, 2020)
Context: Infertility is one of the most painful experiences that can have a negative impact in many areas of an individual’s life. Providing quality care to infertile couples requires health professionals to explore their experiences and needs to plan effective supportive interventions. Objectives: To explore the experiences and needs of Moroccan infertile couples in Assisted Reproductive Technology. Material and Methods: This is a qualitative exploratory study. It involves 40 infertile couples (men and women) and 5 health professionals as key informants. Infertile couples were selected among those attending the first public center for Assisted Reproductive Technology in Morocco located in Rabat during the period 2017-2018. In-depth unstructured interviews, field notes were used with couples and semi-structured interviews with health professionals. The analysis of the interview data was based on a conventional content analysis method. Results: Five types of needs were identified among infertile Moroccan couples, namely: i. Infertility and social support; ii. Infertility and financial support; iii. Infertility and spiritual support; iv. Infertility and informational support; v. Infertility and emotional support. Conclusion: Infertile moroccan couples experienced many emotional, psychosocial and economic difficulties that can negatively affect their quality of life. Thus, to meet the needs and expectations of these couples alongside their medical treatment, it’s necessary to develop couple-centered approaches, which can improve their quality of life, treatment outcomes and mitigate negative psychosocial consequences. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.697-704